2014
DOI: 10.1371/journal.pone.0089355
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation by Deferoxamine Prevents Renal Interstitial Fibrosis in Mice with Unilateral Ureteral Obstruction

Abstract: Renal fibrosis plays an important role in the onset and progression of chronic kidney diseases (CKD). Although several mechanisms underlying renal fibrosis and candidate drugs for its treatment have been identified, the effect of iron chelator on renal fibrosis remains unclear. In the present study, we examined the effect of an iron chelator, deferoxamine (DFO), on renal fibrosis in mice with surgically induced unilateral ureter obstruction (UUO). Mice were divided into 4 groups: UUO with vehicle, UUO with DFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 59 publications
5
64
0
1
Order By: Relevance
“…In keeping with our studies, iron reduction by DFO was found to be effective in mitigating macrophage infiltration, inflammatory cytokines, and adiposity in KKAy mice . DFO was also effective in ameliorating fibrosis in a mouse model of chronic kidney disease . Although these studies and our observations point to the beneficial effects of iron reduction in patients with NAFLD, more studies need to be performed before it is commonly accepted …”
Section: Discussionsupporting
confidence: 88%
“…In keeping with our studies, iron reduction by DFO was found to be effective in mitigating macrophage infiltration, inflammatory cytokines, and adiposity in KKAy mice . DFO was also effective in ameliorating fibrosis in a mouse model of chronic kidney disease . Although these studies and our observations point to the beneficial effects of iron reduction in patients with NAFLD, more studies need to be performed before it is commonly accepted …”
Section: Discussionsupporting
confidence: 88%
“…In addition, while this manuscript was in preparation, it was reported that iron chelation with deferoxamine alleviated renal interstitial fibrosis in mice with unilateral ureteral obstruction. 27 About the difference between dietary iron restriction and iron chelation by the drugs to reduce iron accumulation in the kidney, the effect of dietary iron restriction is to prevent further iron accumulation in the kidney, while that of iron chelation by the drugs is to deprive iron accumulation in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to animal studies, greater suppression of hepcidin in human patients with kidney failure is advantageous in treating renal anemia through correction of iron availability . On the other hand, previous studies have already shown that iron chelation does prevent progression of kidney function in animal models, while results from human studies show that the use of these therapeutic agents ameliorates iron dysmetabolism in renal anemia . But, the use of these agents in humans poses some questions about their safety profile, which makes the case for new therapeutic agents .…”
Section: Manipulating Hepcidin Expression For Therapeutic Purposesmentioning
confidence: 89%